Women Legislators and Economic Performance - Thushyanthan Baskaran; Sonia R. Bhalotra; Brian Min; Yogesh Uppal (Institute of Labor Economics (IZA), 2018)
There has been a phenomenal global increase in the proportion of women in politics in the last two decades, but there is no evidence of how this influences economic performance. We investigate this using data on competitive elections to India's state assemblies, leveraging close elections to isolate causal effects. We find significantly higher growth in economic activity in constituencies that elect women and no evidence of negative spillovers to neighbouring male-led constituencies, consistent with net growth. Probing mechanisms, we find that women legislators are less likely to be criminal and corrupt, more efficacious, and less vulnerable to political opportunism.
Keywords: D72; D78; H44; H73; 330; political representation; identity; India; gender; women legislators; economic growth; luminosity; corruption; roads; close elections